Expression of the Bacillus subtilis acsA Gene: Position and Sequence Context Affect cre-Mediated Carbon Catabolite Repression - Zalieckas, Jill M. (American Society for Microbiology, 1998)
In Bacillus subtilis, carbon catabolite repression (CCR) of many genes is mediated at cis-acting carbon repression elements (cre) by the catabolite repressor protein CcpA. Mutations in transcription-repair coupling factor (mfd) partially relieve CCR at cre sites located downstream of transcriptional start sites by abolishing the Mfd-mediated displacement of RNA polymerase stalled at cre sites which act as transcriptional roadblocks. Although the acsA cre is centered 44.5 bp downstream of the acsA transcriptional start site, CCR of acsA expression is not affected by an mfd mutation. When the acsA cre is centered 161.5 bp downstream of the transcriptional start site for the unregulated tms promoter, CCR is partially relieved by the mfd mutation. Since CCR mediated at an acsA cre centered 44.5 bp downstream of the tms start site is not affected by the mfd mutation, the inability of Mfd to modulate CCR of acsA expression most likely results from the location of the acsA cre. Higher levels of CCR were found to occur at cre sites flanked by A+T-rich sequences than at cre sites bordered by G and C nucleotides. This suggests that nucleotides adjacent to the proposed 14-bp cre consensus sequence participate in the formation of the CcpA catabolite repression complex at cre sites. Examination of CCR of acsA expression revealed that this regulation required the Crh and seryl-phosphorylated form of the HPr proteins but not glucose kinase.